Distinguishing glutamic acid in foodstuffs and monosodium glutamate used as seasoning by stable carbon and nitrogen isotope ratios. Issue 9 (September 2018) - Kobayashi, Kazuhiro; Tanaka, Masaharu; Tanabe, Soichi; Yatsukawa, Yoichi; Tanaka, Mitsuru; Suzuki, Takuya
Abstract: Recently, a number of consumers have begun to appreciate more natural ingredients and have become less willing to consume monosodium glutamate (MSG) as a seasoning. By measuring stable isotope ratios (δ 13 C and δ 15 N) of glutamic acid contained in foodstuffs and MSG used as seasoning, we attempted to distinguish between both using elemental analyzer-isotope-ratio mass spectrometry (EA/IRMS) and gas chromatography/combustion/IRMS (GC/C/IRMS). As a result, seasoning MSG was observed to have a lower δ 15 N value than glutamic acid in foodstuffs. We statistically analyzed the stable isotope ratio data using canonical discriminant analysis, thereby differentiating seasoning MSG from foodstuff-derived glutamic acid at an accuracy of 96.7%. This method is effective for distinguishing glutamic acid in foodstuffs from seasoning MSG.